Electronic Waste and Printed Circuit Board Recycling Technologies - Kaya, Muammer; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers state-of-the-art technologies, principles, methods and industrial applications of electronic waste (e-waste) and waste PCB (WPCB) recycling. It focuses on cutting-edge mechanical separation processes and pyro- and hydro-metallurgical treatment methods. De-soldering, selective dismantling, and dry separation methods (including the use of gravity, magnetic and electrostatic techniques) are discussed in detail, noting the patents related to each. The volume discusses the available industrial equipment and plant flowsheets used for WPCB recycling in detail, while addressing potential future directions of the field. This practical, comprehensive, and multidisciplinary reference will appeal to professionals throughout global industrial, academic and government institutions interested in addressing the growing problem of e-waste. Covers principles, methods and industrial applications of e-waste and PCB recycling; Details state-of-the-art mechanical separation processes and pyro- and hydro-metallurgical treatment methods; Describes the available industrial equipment used and plant flowsheets for PCB recycling and addresses potential future developments of this important field.
E-waste definition and classifications -- E-waste concerns and challenges -- E-waste sources and values -- E-waste economics -- Printed Circuiot Boards (PCBs) Characteristics and Assembly -- Manual/Semi/Automatic Disassembling/Dismantling (Thermal and Chemical Desoldering and Dismantling) of PCBs -- Mechanical/Physical Separation Techniques for PCBs (Shredding, Pulverizing, Smashing, Delamination, Classification, Filtration, Gravity Separation, Magnetic Separation, Electrostatic Separation) -- Pyrometallurgical Recycling Techniques (Integrated Smelting and Refining) of Base, Precious and Special Metals from PCBs -- Hydrometallurgical Approaches for Recycling Metals, Rare Earth Elements and Precious Metals from PCBs -- Biohydrometallurgical Approaches for Metals, Rare Earth Elements and Precious Metals from PCBs -- Current Global Best Industrial Practices for PCB Recycling -- Challenges and Future Trends in E-Waste/PCB Recycling.
Keywords: Materials -- Analysis; Materials; Refuse and refuse disposal; Industrial management -- Environmental aspects; Building materials; Characterization and Analytical Technique; Materials Engineering; Waste Management/Waste Technology; Corporate Environmental Management; Structural Materials